PC ‘Aisyiyah Ngampilan institutional strengthening through effective organizational communication - Adhianty Nurjanah; Nano Prawoto (Community Empowerment, 2023)
The organizational problem of ‘Aisyiyah Branch Leadership (PCA) Ngampilan is the diversity of the community which is often referred to as the "abangan" area because there are still many people whose lifestyle is still dominated by pre-Islamic Javanese traditions. In dealing with this situation, PCA Ngampilan must have strong institutional values, one of which is strengthening organizational communication. The purpose of this activity is to increase the understanding of leaders within the organization and internal organizational communication regarding the use of social media. Activities are carried out in several stages, namely initial assessment, socialization, training, mentoring, and evaluation. The community service program went very well where PCA Ngampilan's knowledge related to leadership in organizational communication and the use of social media increased by up to 85%.